The Influence of Maternal Parenting Style and School-Focused Parenting Practices on Student Engagement - Duriano, Trisha Mae; Balancio, Mark Raven; Bustamante, Eloisa; Roca, Cherrie Rose; Salvatin, John Vincent; Sigua, Akia Kyle; Paloga, Crislyn Alpha (Journal of Interdisciplinary Studies in Education, 2026)
This study focused on the influence of maternal parenting style and school-focused parenting practices on student engagement. It aimed to help instill knowledge and insight in mothers regarding their parenting style and school-focused parenting practices for their children. The respondents in this research were 318 mothers and 318 third-grade learners in 4 public schools in Philippines. The researchers used a quantitative correlational design, median, and interquartile range (IQR). The results of the study revealed that there was no significant relationship or influence of maternal parenting style or school-focused parenting practices on student engagement.